THE CONCEPT OF TAX IN THE PERSPECTIVE OF ABU UBAID : A Relevance With The Tax System In Indonesia - Musa, Armiadi; Binti Ilyas, Irawati; Khalidin, Bismi (Program Studi Hukum Ekonomi Syariah Fakultas Syariah dan Hukum UIN Ar-Raniry, 2023)
This article examined if the implementation of tax policies in Indonesia adopts the Islamic concepts or not. In doing so, the article refers to Ubaid’s concepts on tax collection as advocated in the Islamic community. The main concern of the article was at exploring realities and practices during the implementation of tax policies to the Indonesian citizens, which in turns affecting the Muslim societies as well. This inquiry was explored usingqualitative method, in which the socio-economics approach was used as the basis of analysis. The data was collected using interviews of reputable figures in the field of Islamic economics and tax policies. The research findings disclosed that the Indonesian tax policies have partially adopted the Ubaid’s concepts on tax collection. In term of legal sources, the Indonesian tax policies have fully referred to the Indonesian tax law, and few of them have similarities with Ubaid’s concepts of the tax collection.